Evaluating the National Surgical Quality Improvement Program-Pediatric Surgical Risk Calculator for Pediatric Craniosynostosis Surgery. Issue 6 (September 2018) - Gadgil, Nisha; Pan, I-Wen; Babalola, Solomon; Lam, Sandi
Abstract : Background: The American College of Surgeons' National Surgical Quality Improvement Program-Pediatric (NSQIP-P) risk calculator was developed based on national data. There have been no studies assessing the risk calculator's performance in pediatric neurosurgery. The authors aimed to evaluate the predictions from the risk calculator compared to our single institution experience in craniosynostosis surgery. Methods: Outcomes from craniosynostosis surgeries performed between 2012 and 2016 at our academic pediatric hospital were evaluated using the NSQIP-P risk calculator. Descriptive statistics were performed comparing predicted 30-day postoperative events and clinically observed outcomes. The performance of the calculator was evaluated using the Brier score and receiver operating characteristic curve (ROC). Results: A total of 202 craniosynostosis surgeries were included. Median age was 0.74 years (range 0.15–6.32); 66% were males. Blood transfusion occurred in 162/202 patients (80%). The following clinical characteristics were statistically correlated with surgical complications: American Society of Anesthesiologists physical status classification >1 ( P < 0.001), central nervous system abnormality ( P < 0.001), syndromic craniosynostosis ( P = 0.001), and redo operations ( P = 0.002). Postoperative events occurred in <3%, including hardware breakage, tracheal-cartilaginous sleeve associated with critical airway, and surgical site infection. The calculator performed well in predicting any complication (Brier = 0.067, ROC = 73.9%), and for pneumonia (Brier = 0.0049, ROC 99%). The calculator predicted a low rate of cardiac complications, venous thromboembolism, renal failure, reintubation, and death; the observed rate of these complications was 0. Conclusions: The risk calculator demonstrated reasonable ability to predict the low number of perioperative complications in patients undergoing craniosynostosis surgery with a composite complications outcome. Efforts to improve the calculator may include further stratification based on procedure-specific risk factors.